ANALISA EVALUASI SDM TERHADAP KUALITAS KERJA ASN KANTOR CAMAT KEMPAS - Rita Seriani; Yaswar Aprilian; Zainal Arifin (AMNESIA (JURNAL MANAJEMEN SUMBER DAYA MANUSIA), 2026)
This study aims to analyze the effect of human resource evaluation on the work quality of State Civil Apparatus (ASN) at the Kempas Sub-District Office. Human resource evaluation is an important factor in improving the work quality of ASN to ensure optimal public service delivery. This research employs a quantitative method with a descriptive and associative approach. The population of this study consists of all ASN at the Kempas Sub-District Office, totaling 48 employees, all of whom were selected as the research sample using a saturated sampling technique. Data were collected through questionnaires, observations, and documentation. The data were analyzed using validity tests, reliability tests, classical assumption tests, and simple linear regression analysis with the assistance of SPSS software. The results indicate that human resource evaluation has a positive and significant effect on the work quality of ASN at the Kempas Sub-District Office. Therefore, better implementation of human resource evaluation will lead to improved ASN work quality in carrying out their duties and responsibilities.